الإسلام دين السلام - Shumsudin Yabi; A. Irwan Santeri Doll Kawaid; Akila Mamat; Muhammad Yosef Niteh (Fakulti Pengajian Quran dan Sunnah, 2024)
8TH International Prophetic Conference SWAN 2022 5th to 6th October 2022 (Hybrid Conference) Organized by: Faculty Of Quranic And Sunnah Studies